Application of GNSS technology in surface mining. Issue 4 (1st October 2016) - Vrublová, Dana; Kapica, Roman; Gibesová, Beáta; Mudruňka, Jaroslav; Struś, Adam
Abstract: VŠB – Technical University of Ostrava, institute of geodesy and mine surveying has been cooperating with Severočeské doly j.s.c. (SD) in important research project since 2007. The main goal is improve control system for opencast mining. Two bucket wheel excavators (K800/103 and KU300/27) were equipped with measurement hardware at the Libouš Lignite Mine (North Bohemia brown coal basin). The position of the bucket wheel centre is computed by means of GNSS data, inclinometer and incremental measurements. Data is transferred to a base. All the values measured are saved in this database. The surface layout of the mine as well as positions of underground geological layers are updated on a regular basis in the digital model of the mine. The main aim of the research is verifying the system in connection to digital model for short time prognosis of qualitative parameters of coal (Ad, Sd, Qr, Wr and MS), continuous automatic computation of mined materials (m3, tons) and continuous checking of creation of the movement surface/plane of the excavator and mining goals. Mine surveyors have a lead role in the working team. The paper describes possibilities of using the GNSS for mine surveying and for production planning.